Ultrafast excited states dynamics of [Ru(bpy)3]2+ dissolved in ionic liquids. Issue 41 (10th October 2016) - Borgwardt, Mario; Wilke, Martin; Kiyan, Igor Yu.; Aziz, Emad F.
Abstract : In this work, we demonstrate the potential of room-temperature ionic liquids as solvents to investigate the excited states dynamics of [Ru(bpy)3 ] 2+ by means of time-resolved photoelectron spectroscopy. Abstract : Room-temperature ionic liquids (ILs) represent a well-known class of materials exhibiting extremely low vapor pressures and high electrochemical stability. These properties make ILs attractive for various applications requiring UHV conditions. Here, we apply 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [EMIM][TfO] as a solvent to investigate the excited state dynamics of the transition metal complex [Ru(bpy)3 ] 2+ with the use of ultrafast XUV photoelectron spectroscopy. This study is aimed to reveal the effect of the IL environment when the frontier molecular orbitals and the states dynamics of the solute need to be addressed. By initiating the electron dynamics with a pump laser pulse of 480 nm wavelength, we can unambiguously characterize the kinetics of the excited states of [Ru(bpy)3 ] 2+ and determine their absolute binding energies. From a global fit analysis of the transient signal, the binding energies of the initially populated metal-to-ligand charge-transfer state 1 MLCT and the thermally relaxed 3 MLCT are inferred to be −0.2 eV and 0.3 eV, respectively. A three-state model, including the intersystem crossing (ISC) from the 1 MLCT to the 3 MLCT state and the intramolecular vibrational relaxation (IVR) within the triplet configuration, is used to describe the involved decay processes. The kinetic constants of (37 ± 10) fs for the ISC and (120 ± 20) fs for the IVR are found to be in agreement with the values previously reported for aqueous solution. The obtained results open up exciting new possibilities in the field of liquid phase spectroscopy.